Isolation, identification, biological characteristics, and antifungal efficacy of sodium bicarbonate combined with natamycin on Aspergillus niger from Shengzhou nane (Prunus salicina var. taoxingli) fruit - Guo, Tian-Rong; Zeng, Qing; Yang, Guo; Ye, Si-Si; Chen, Zi-Yi; Xie, Shi-Ying; Wang, Hai; Mo, Yi-Wei (Frontiers in Microbiology, 2023)
The fungi causing fruit rot were isolated from symptomatic Shengzhou nane (Prunus salicina var. taoxingli) fruit and identified as Aspergillus niger by biological characteristics and molecular analysis of the internal transcribed spacer region (rDNA-ITS) and translation elongation factor-1α (TEF-1α) sequences. Optimal growth conditions for A. niger were 30°C, pH 5.0–6.0, and fructose and peptone as carbon and nitrogen sources. The effects of sodium bicarbonate (SBC), natamycin (NT) and combined treatments on A. niger inhibition were investigated. Treatment with 4.0 g L−1 sodium bicarbonate (SBC) + 5.0 mg L−1 natamycin (NT) inhibited mycelial growth and spore germination as completely as 12.0 L−1 SBC or 25.0 mg L−1 NT. SBC and NT treatments disrupted the structural integrity of cell and mitochondria membranes and decreased enzyme activities involved in the tricarboxylic acid (TCA) cycle, mitochondrial membrane potential (MMP), ATP production in mitochondria, and ergosterol content in the plasma membrane, thus leading to the inhibition of A. niger growth. Moreover, experimental results in vivo showed that the rot lesion diameter and decay rate of Shengzhou nane fruit treated with SBC and NT were significantly reduced compared with the control. The results suggest that the combination treatment of SBC and NT could be an alternative to synthetic fungicides for controlling postharvest Shengzhou nane decay caused by A. niger.